Communication of Gender Equality in Municipalities in Lithuania - Stundžė, Lijana; Novelskaitė, Aurelija; Adomaitienė, Reda (Information & Media, 2024)
Legal documents in Lithuania – the Law on Equal Opportunities, the Law on Equal Opportunities for Women and Men, the Law on Local Self-Government, the Labor Code – establish the obligation to implement gender equality policy at the level of self-government. Municipalities, as providers of services to residents, must integrate the gender aspect into local self-government documents and ensure the implementation of gender equality principles in daily practices. However, as the results of previous studies show, these processes in municipalities take place slowly (if at all). Striving to contribute to the accumulation of knowledge about the situation of gender equality in municipalities in Lithuania and to take a deeper look at the communication processes within the municipality, the purpose of this paper is to describe the peculiarities of the gender equality communication in Lithuanian municipalities. Empirically, the paper is based on the analysis of the semistructured interview data collected in ten Lithuanian municipalities in 2019 by employing the discourse analysis approach. The analysis of the selected interview material showed that the discourse of gender equality in municipalities is developed by different “speakers” on the overlapping dimensions such as: organizational and individual communication, both of which can take formal as well as informal forms; information transfer vs. exchange of information; information as ground for action and ignorance information; etc. The results of the analysis prove that “talking” can both enable and block the action, and the fact that positions of authoritative power remain in the formal hierarchies of the institution in this communication indicates the need to look for additional measures for the effective implementation of gender equality.